2022
DOI: 10.3390/jimaging9010008
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Method for Vickers Hardness Estimation by Image Processing

Abstract: Hardness is one of the most important mechanical properties of materials, since it is used to estimate their quality and to determine their suitability for a particular application. One method of determining quality is the Vickers hardness test, in which the resistance to plastic deformation at the surface of the material is measured after applying force with an indenter. The hardness is measured from the sample image, which is a tedious, time-consuming, and prone to human error procedure. Therefore, in this w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…Previous studies employing image processing techniques, like those by Polanco et al [10], reported hardness measurement errors ranging from 0.32% to 4.5% for both manual and their proposed methods, with an average processing time of 2.05 s. Similarly, Buitrago et al [19] utilized convolutional neural networks (CNNs) and achieved manual hardness errors between 0.17% and 5.98%, with an average execution time of 6 s. Our proposed method demonstrates comparable error margins to these existing approaches, while significantly reducing processing time, thereby leading to lower computational costs.…”
Section: Model Testing and Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies employing image processing techniques, like those by Polanco et al [10], reported hardness measurement errors ranging from 0.32% to 4.5% for both manual and their proposed methods, with an average processing time of 2.05 s. Similarly, Buitrago et al [19] utilized convolutional neural networks (CNNs) and achieved manual hardness errors between 0.17% and 5.98%, with an average execution time of 6 s. Our proposed method demonstrates comparable error margins to these existing approaches, while significantly reducing processing time, thereby leading to lower computational costs.…”
Section: Model Testing and Validationmentioning
confidence: 99%
“…ML techniques also enable the classification of material defects, such as fractures or surface stains [4][5][6], or the prediction of coating properties like hardness, friction coefficient, corrosion rate, based on deposition parameters [7][8][9]. One way to control material quality and ensure it meets the appropriate characteristics for its application is through the Vickers hardness test [10]. This test involves measuring the plastic deformation or indentation mark produced on the surface after applying a load with a pyramidal diamond indenter, and the hardness value is determined by Equation (1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5] uses sensor images for real-time strain prediction. Material hardness detection has been investigated using image processing techniques such as [35].…”
Section: Related Workmentioning
confidence: 99%
“…Polanco et al employed thresholding and mathematical morphology techniques for edge determination and introduced a quadrature index to choose among methods: maximum local radius, perimeter, and Hough transform, which yielded the best result. They obtained the Vickers hardness value with an error of 4.5% compared to manual measurements [11].…”
Section: Introductionmentioning
confidence: 99%